2022
DOI: 10.1021/acsomega.2c04518
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and LOX Enzyme Inhibitions of Different Lavender Essential Oils and Major Components Linalool and Camphor

Abstract: In this present study, Lavandula angustifolia, Lavandula stoechas, and Lavandula × heterophylla essential oils and their main compounds linalool and camphor were evaluated in vitro for lipoxygenase enzyme (LOX) and for angiotensin converting enzyme 2 (ACE2) inhibition potential. The chemical compositions of L. angustifolia, L. stoechas, and L. heterophylla essential oils were confirmed both by gas chromatography−mass spectrometry and gas chromatography−flame ionization detection, where 22.4, 0.9, and 30.6% lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Furthermore, 3,5- O -dicaffeoylquinic acid, another phenolic compound abundant in the prepared H. italicum extracts [ 10 ], is also a potent 5-LOX inhibitor [ 80 ]. Finally, according to previous studies, essential oil components, such as linalool, may also contribute to the anti-LOX activity [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 3,5- O -dicaffeoylquinic acid, another phenolic compound abundant in the prepared H. italicum extracts [ 10 ], is also a potent 5-LOX inhibitor [ 80 ]. Finally, according to previous studies, essential oil components, such as linalool, may also contribute to the anti-LOX activity [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature reports supported these findings concerning other medicinal plants. Indeed, several studies have reported the chemical composition of LSEO, with some indicating that, in addition to the fenchone/camphor chemotypes, the chemical compositions of LSEO collected in Morocco and Greece contained 1,8-cineole and camphene, and α-cardinol, respectively, while others disclosed the presence of myrtenyl acetate, bornyl acetate, linalyl acetate, camphene, linalool, borneol, γ-terpinene, lavandulyl acetate, and caryophyllene as major compounds [ 10 , 18 , 43 , 44 , 45 , 46 ]. Besides the presence of some main compounds, our study clearly revealed the chemical composition quantitative and qualitative variability of L. stoechas plants collected from three different regions.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed in triplicate, and the average results were reported as previously. 32 3.7. p38MAPK Enzyme Inhibitory Assay. The ELISA Kit (Invitrogen) was applied in accordance with the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Nordihydroguaiaretic acid (NDGA) was used as a positive control. Experiments were performed in triplicate, and the average results were reported as previously …”
Section: Methodsmentioning
confidence: 99%